Controlling monetary aggregates II: the implementation; proceedings - Federal Reserve Bank of Boston (Boston : Federal Reserve Bank of Boston, 1972)
This is a sponsored series of conferences on important monetary issues. All papers were presented by persons from within the Federal Reserve System and discussants were primarily academicians.
usc 18/08/17
Loans
Keywords: Monetary policy; Money; United States